Русская трагедия: Пьеса А.Н. Островского "Гроза" в русской критике и литературоведении (Круг чтения, 2002)
Экземпляры: (20110301) / Инвентарный номер: 46366 / Цена: 15.00 / Сис.шифр: 83.3 / Авт.знак: Р89 / ББК: 83.3